Sexual behaviors and Practices among university students Prácticas y comportamientos sexuales en estudiantes universitarios - MANRIQUE ABRIL FRED GUSTAVO; OSPINA DÍAZ JUAN MANUEL (Universidad Nacional de Colombia, 2007)
Introduction: Since 1995 we validated descriptive studies, as a need to research prior educational interventions, given the cultural plurality that disqualifies the application of universal models in as far as sexual education. Purpose: Describing practices and sexual behavior of university students of the UPTC, in the city of Tunja. Methods: transversal cut, sequential sampling study with a sample of 764 students. In the Epiinfo 2002® they estimated frequencies, cross variables, percentages. Results: Average age: 20,4 years; 56,7% females; 82,8% lower middle class; 79,7% catholic o Christian; when solving intimacy matters, 11,4% trust the father, 33,5% on the mother; only 36,2% have 100% certainty to avoidaundesiredpregnancy and 27% in contracting a STD. 61,2% considers necessary to increase sexual knowledge; 40,5% has had at least one alcohol loss of memory; 30% has had undesired sex, at least once, under the effect of alcohol. Global reason for fertility: 25,4%. 45,3% of pregnancies end up in undesired miscarriages. Conclusions: Most relevant Problems: high rate of fecundity, birth and induced abortions, high alcohol consumption. Introducción: Desde 1995 se validaron estudios de tipo descriptivo, como necesidad de investigar previamente a las intervenciones educativas, dada la pluralidad cultural que descalifica modelos de aplicación universal en lo referente a la educación sexual. Objetivo: Describir prácticas y comportamientos sexuales en estudiantes universitarios de la UPTC de Tunja. Métodos: Estudio de corte transversal, muestreo secuencial, muestra de 764 estudiantes. En Epiinfo 2002® se estiman frecuencias, cruce de variables, porcentajes. Resultados: Edad promedio: 20,4 años; 56,7% mujeres; 82,8% clase media-baja; 79,7% católico o cristiano; para resolver intimidades, 11,4% confía en el padre, 33,5% en la madre; apenas 36,2% tiene 100% de certeza de evitar un embarazo no deseado y27%,de contraeruna ETS. 61,2% considera necesario incrementar sus conocimientos sexuales; 40,5% ha tenido al menos una laguna alcohólica; 30% ha tenido sexo no deseado, al menos una vez, bajo el efecto del alcohol. Razón global de fertilidad: 25,4%. 45,3% de embarazos termina en aborto provocado. Conclusiones: Problemas más relevantes: altas tasas de fecundidad, natalidad y aborto provocado, elevado consumo de alcohol.